Sexual abuse - Healey, Justin (Rozelle, N.S.W. : Spinney Press, 2003)
Sexual abuse is a confronting yet often hidden crime in our society, leaving victims to often experience ongoing suffering and trauma, and many perpetrators unpunished by the law. This book looks at the extent, types and signs of sexual assault which can occur; the legal process involving the reporting and prosecution of sexual violence; how to reduce the risk of being exposed to sexual assault such as date rape and child sexual abuse; child sexual abuse and paedophile awareness; and helping survivors to cope with past abuse.
Chapter 1: Sexual Assault: What is sexual assault?; Trends in sexual assault; Sexual assault; Definition of sexual assault; Rape; Sexual abuse of men and boys; Date rape rarely reported: study; Friends look after friends; Alarming picture of teenage sexual violence in report; Information for adult survivors of sexual assault; Sexual assault and the law; Impact of sexual assault; Supporting survivors of sexual assault. -- Chapter 2: Child Sexual Abuse: Child sexual assault; Child sexual abuse - the facts; Possible signs of sexual abuse; Keeping children safe from sexual abuse; Behavioural indicators of child sexual abuse; What are the effects of child sexual assault?; How does a child live with this sort of pain?; Boys the silent victims of sexual abuse; Silent majority: women kept quiet on sexual abuse; Children safer on this side of the white picket fence; Information about child sex offenders; Paedophiles; Information for adults who experienced abuse as a child; Information for survivors of childhood sexual assault.
Includes index.
Bibliography: p. 43.
For senior secondary and tertiary students
Keywords: Sex crimes -- Australia; Child sexual abuse; Sexual abuse victims; Sex crimes -- Prevention